2020
DOI: 10.3390/ijms21218050
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Autophagy-Notch1-Mediated NLRP3 Inflammasome Activation to Chronic Inflammation and Fibrosis in Keloid Fibroblasts

Abstract: Keloid is a representative chronic fibroproliferative condition that occurs after tissue injury. Emerging evidence showed that activation of NACHT, LRR, and PYD domains-containing protein 3 (NLRP3) inflammasome is involved in the pro-inflammatory response in injured tissues. However, the role of NLRP3 inflammasome in keloid progression remains unclear. Notch signaling, which activates NLRP3 inflammasome, is known to contribute to scar formation in keloid, but the cause of enhanced Notch signaling in keloid is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 37 publications
1
36
0
Order By: Relevance
“…Moreover, in vitro experiments demonstrated that overexpression of NLRP3 could partially reverse the effects of hsa_circ_0002198 on keloid fibroblast cell proliferation, migration, and invasion, as well as the levels of TGF-β, Col I, α-SMA, and caspase 3 proteins in human keloid fibroblasts. A recent study by Lee et al (2020) not only showed that NLRP3 inflammasomes are activated in keloid fibroblasts and involved in chronic inflammatory processes, but also that NLRP3-dependent IL-1β release may aggravate tissue damage, prolong inflammatory responses, and adversely affect remodeling by inducing continuous myofibroblast differentiation in keloids (Lee et al, 2020). Accumulated evidence has elucidated how circRNAs help to regulate NLRP3 inflammasomes in various diseases, such as depression (Zhang et al, 2019), preeclampsia (Li et al, 2020b), diabetes mellitus (Cheng et al, 2019), and traumatic brain injury (Li et al, 2020a).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in vitro experiments demonstrated that overexpression of NLRP3 could partially reverse the effects of hsa_circ_0002198 on keloid fibroblast cell proliferation, migration, and invasion, as well as the levels of TGF-β, Col I, α-SMA, and caspase 3 proteins in human keloid fibroblasts. A recent study by Lee et al (2020) not only showed that NLRP3 inflammasomes are activated in keloid fibroblasts and involved in chronic inflammatory processes, but also that NLRP3-dependent IL-1β release may aggravate tissue damage, prolong inflammatory responses, and adversely affect remodeling by inducing continuous myofibroblast differentiation in keloids (Lee et al, 2020). Accumulated evidence has elucidated how circRNAs help to regulate NLRP3 inflammasomes in various diseases, such as depression (Zhang et al, 2019), preeclampsia (Li et al, 2020b), diabetes mellitus (Cheng et al, 2019), and traumatic brain injury (Li et al, 2020a).…”
Section: Discussionmentioning
confidence: 99%
“…The highly conserved Notch gene family was first discovered in Drosophila melanogaster by Morgan et al in 1917, and comprises four transmembrane receptors, Notch1, Notch2, Notch3 and Notch4, which are involved in regulating the viability, proliferation and differentiation of cells and the development of organs (Nantie et al 2014;Ebens & Maillard, 2013). Previous studies have reported that the upregulated expression of Notch1 promoted the autophagy of cells (Xu et al 2019, Lee et al 2020. Similarly, the results of the present study also showed that the protein expression levels of Notch1 were significantly increased Ole treated groups.…”
Section: Expression Levels Of Lc3b Protein In Hacat Cell Psoriasis Modelmentioning
confidence: 99%
“…The dermis of KD is characterized by abundant thick hyalinized collagen bundles, also known as “keloidal collagen”, and by the persistence of myofibroblasts, and is surmounted by a thickened epidermis which undergoes accelerated differentiation [ 166 ]. Though Notch signalling has been less investigated in KD than in other fibrotic skin diseases, available experimental evidences support its involvement in KD pathomechanisms [ 174 , 175 ]. A study by Syed and Bayat revealed that (i) NOTCH1, NOTCH2 and JAG1 mRNA and protein levels are significantly up-regulated in KD skin biopsies and primary FBs from KD patients (KD FBs) with respect to healthy tissues and FBs, respectively; (ii) Notch pathway stimulates cell proliferation, migration, invasion and angiogenetic properties of cultured KD FBs; and (iii) Notch activation positively correlates with inflammatory degree in KD tissues, suggesting that immune cells might turn on Notch cascade in vivo [ 174 ].…”
Section: Notch Expression and Role In Skin Physiology And Pathologymentioning
confidence: 99%
“…Furthermore, a recent study reported that KD FBs from subjects affected with active KD ( i.e. patients with a recent keloid and complaining keloid pruritus and pain) exhibit a more prominent NOTCH1 activation as compared to KD patients with stable lesions [ 175 ]. In addition, KD FBs were hallmarked by: (i) a reduced autophagic flux, which has been associated with a reduced autophagy-mediated degradation of Notch, and (ii) a NOTCH1-mediated induction of α-SMA, TGF-β3 and NLRP3 (NACHT, LRR and PYD domains-containing protein 3) inflammasome, which primes the inflammatory cascade in KD.…”
Section: Notch Expression and Role In Skin Physiology And Pathologymentioning
confidence: 99%
See 1 more Smart Citation